Arbuscular mycorrhizal fungi alter above- and below-ground chemical defense expression differentially among Asclepias species - Vannette, Rachel L.; Hunter, Mark D.; Rasmann, Sergio (Frontiers in Plant Science, 2013)
Belowground symbionts of plants can have substantial influence on plant growth and nutrition. Recent work demonstrates that mycorrhizal fungi can affect plant resistance to herbivory and the performance of above and belowground herbivores. Although these examples emerge from diverse systems, it is unclear if plant species that express similar defensive traits respond similarly to fungal colonization, but comparative work may inform this question. To examine the effects of arbuscular mycorrhizal fungi (AMF) on the expression of chemical resistance, we inoculated 8 species of Asclepias (milkweed)--which all produce toxic cardenolides--with a community of AMF. We quantified plant biomass, foliar and root cardenolide concentration and composition, and assessed evidence for a growth-defense tradeoff in the presence and absence of AMF. As expected, total foliar and root cardenolide concentration varied among milkweed species. Importantly, the effect of mycorrhizal fungi on total foliar cardenolide concentration also varied among milkweed species, with foliar cardenolides increasing or decreasing, depending on the plant species. We detected a phylogenetic signal to this variation; AMF fungi reduced foliar cardenolide concentrations to a greater extent in the clade including A. curassavica than in the clade including A. syriaca. Moreover, AMF inoculation shifted the composition of cardenolides in above- and below-ground plant tissues in a species-specific fashion. Mycorrhizal inoculation changed the relative distribution of cardenolides between root and shoot tissue in a species-specific fashion, but did not affect cardenolide diversity or polarity. Finally, a tradeoff between plant growth and defense in non-mycorrhizal plants was mitigated completely by AMF inoculation. Overall, we conclude that the effects of AMF inoculation on the expression of chemical resistance can vary among congeneric plant species, and ameliorate tradeoffs between growth and defense.